Women Satisfaction with Quality of Postnatal Care in the Ledzokuku Krowor Municipal Assembly (Lekma) Hospital - Asem, C.K. (University of Ghana, 2016)
Background: The postnatal period is a very crucial period for both mother and baby. In Ghana however, postnatal care (PNC) coverage is low – 36% of postpartum mothers did not receive postnatal care at all in 2013 - as compared to other maternal health services like antenatal care (ANC). This study explored women‟s perceived quality of postnatal care and level of satisfaction in the Ledzokuku Krowor Municipal Assembly (LEKMA) hospital. Methods: A cross sectional study of 300 women was conducted at the LEKMA hospital. Structured questionnaires based on Donabedian‟s framework for assessing quality of care, were used to obtain data on women‟s perception and satisfaction with quality of postnatal care. Descriptive statistics was used to show the distribution of explanatory variables and bivariate logistic regression was used to investigate associations between indicators of quality of care, level of satisfaction and utilisation of PNC services. Results: The results show that 92% of women were satisfied with the postnatal services. Most of them were satisfied with the cleanliness of the environment, clarity of diagnosis, interpersonal behaviour, and availability of medicines and laboratory services. All of the socio-demographic characteristics, except age, had no significant relationship with women‟s perception of quality of postnatal care. Conclusion: There is need for more interventions to further improve and sustain the quality of postnatal care provided to postpartum women at the LEKMA hospital.
Thesis(MPH)-University of Ghana, 2016
Keywords: Postnatal Care; Women Satisfaction